2009
DOI: 10.1007/s10029-009-0602-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bowel resection and outcome in patients with incarcerated groin hernias

Abstract: Risk for intestinal resection in emergency groin hernia repair is higher in patients with femoral hernia, obvious peritonitis, or those with no health insurance. Surgeons should pay more attention to these patients and initiate emergency surgery without delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 19 publications
2
50
0
1
Order By: Relevance
“…The rate of incarcerated groin hernias changes by countries. Ge et al found this rate 12,8% in China [16], Nilsson et al found 6% [17], and Bickell et al found 13% [18]. Ge et al concluded that the main causes of high incarceration rates are economic problems and lack of insurance [16].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of incarcerated groin hernias changes by countries. Ge et al found this rate 12,8% in China [16], Nilsson et al found 6% [17], and Bickell et al found 13% [18]. Ge et al concluded that the main causes of high incarceration rates are economic problems and lack of insurance [16].…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies report femoral hernia and delaying visits to physicians can increase the risk of bowel resection (25)(26)(27).…”
Section: Bowel Resectionmentioning
confidence: 99%
“…A retrospective study was recently published evaluating the risk factors associated with bowel resection and treatment outcome in patients with incarcerated groin hernias [14]. …”
Section: Recommendationsmentioning
confidence: 99%
“…Of these patients, bowel resection was required in 15.4% of cases (28/182). A logistic regression model identified three independent risk factors for bowel resection: lack of health insurance (odds ratio [OR], 5, P = 0.005), obvious peritonitis (OR, 11.52, P = 0.019), and femoral hernia (OR, 8.31, P < 0.001) [14]. …”
Section: Recommendationsmentioning
confidence: 99%